Technically Speaking, What Is Sturgeon Caviar? - Frank A. Chapman; Joel P. Van Eenennaam (EDIS)
People all over the world eat fish and shellfish eggs. Seafood roes are among the most valuable of fishery commodities because they are considered a delicacy and sell for a high price. The eggs can be acquired as whole roe, (the eggs still attached to the ovary, as with mullet), or as individual eggs that may be collected directly from where the female deposits or spawns her eggs (for instance, “tobiko,” from flying fish), or by harvesting the female and separating the eggs from the ovary (as with salmon, lumpfish, and sturgeon “caviar”). The most sought-after and high-valued of all seafood roes are the eggs obtained from the sturgeon. Traditionally coveted by royalty and the aristocracy, sturgeon caviar today is prized by chefs and discerning food connoisseurs the world over for its delicate flavor and nutrient-rich health benefits. Learn what caviar is, find out how it’s collected, and discover more about the fascinating sturgeon fish in this 4-page fact sheet written by Frank A. Chapman and Joel P. Van Eenennaam, and published by the School of Forest Resources Program in Fisheries and Aquatic Sciences, June 2016.